Propuesta de un sistema de administración y gestión para aplicar en la unidad educativa Santa María Eufrasia - Olivares Rosado, Johanna Mariuxi (2014)
This thesis was carried out based on an investigation into UESME and consulting different authors addressing the administration and management. Beginning from the administration and management system that. The aim is improve the system with the implementation of administrative processes and educational quality standards working in the country. The problem starts from the improvement of the administration in accordance with the current regulations for the new institution. The causes and limitations are discussed. The objectives guide the work toward the development of an administrative and management model. The framework covers all scientific management fundamentals and processes; educational administration and implementation in institutions, in what has to do with the planning, organization, evaluation and administration and management system applied to the institution. The educational administrator has to fulfill all requirements and profiles to be successful in their role.